Do informational nudges alter firms' hiring behavior of older workers? - Pia Homrighausen; Julia Lang (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper analyses a local marketing campaign that provided information about unproven age-re-lated stereotypes and the value of older workers in Germany. The campaign was designed to increase the hiring rate of older workers. Using comprehensive register data, we find that the information provided by the campaign (via banners, interviews, job fairs and information brochures) did change firms' employment behavior. The cheap and mild intervention increased the employment rate of older workers on average by 3 percentage points. This increase, however, is attributable to an increase in job stability rather than to an increase in the hiring of older workers.
Keywords: D83; J21; J23; J64; J78; 330; Unemployment; Nudge; Information; Older workers; Stereotypes; Difference-in-differ-ences